Classroom Management in Elementary Physical Education: A Management Function Perspective - Novi Silvia Mulyani; Hanafiah Hanafiah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to analyze the implementation of classroom management functions in Physical Education, Sports, and Health (PJOK) to create a conducive learning environment in elementary schools. A qualitative case study design was employed in two public elementary schools in Cianjur Regency, namely SDN Murnisari and SDN Dewi Sartika. The participants included two PJOK teachers, two school principals, and students, selected as supporting informants purposively for their involvement in the learning process. The study was conducted over three months from February to April 2025. Data were collected through in-depth interviews, participatory observation, and document analysis. Data validity was ensured through triangulation of sources and techniques, member checking, and prolonged engagement. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that the classroom management functions of planning, organizing, actuating, and controlling were implemented systematically in both schools. However, differences influenced them in resource availability and institutional support. Teachers in resource-limited settings relied on adaptive strategies, while those in well-supported environments implemented more structured and varied learning approaches. This study contributes by providing a comprehensive understanding of how classical management functions are operationalized in PJOK learning and offers practical insights for developing inclusive and conducive learning environments in elementary education.